Blockchain Based Real-Time Contact Tracing – A Secure Way to Mitigate Highly Infectious Diseases - Bandyopadhayay, Asit; Mitra, Reshmi; Bandyopadhayay, Srija (Journal of Applied Business and Economics, 2023)
Contact tracing is an effective, data driven infectious disease control strategy that involves identifying cases of active virus carriers and their contacts in restricting further disease transmission. Despite the effectiveness of this strategy, there are serious concerns regarding the privacy and security of data that are collected in this process as individuals give up control over those data. This study aims to provide some building blocks for developing a secured blockchain-based mobile application for contract tracing to strengthen the infectious disease mitigation approach. It also attempts to understand the contrasting perspective of different stakeholders involved in the data collection process through stakeholder survey and their willingness to share/store identity and health-related data in a blockchain-based app. Finally, we suggest a framework in developing an app to automate contract tracing in a private, secure, maintainable environment. This study helps create a strategic roadmap for developing a secured contact tracing platform to mitigate highly communicable diseases.